GLUCOCORTICOIDS IN THE THERAPY OF SYSTEMIC LUPUS ERYTHEMATOSUS - T. M. Reshetnyak; N. V. Seredavkina; I. S. Dydykina; E. I. Nasonov (Klinicist, 2014)
Despite a more than fifty-year period after the introduction of glucocorticoids (GCs) into therapeutic practice; they have headed the list of anti-inflammatory drugs so far. The paper analyzes current views on the terminology of GCs, mechanism of action, standardization of indications for their use in systemic lupus erythematosus, choice of a dose and a regimes of the drugs, as well as the rates of their decrease; the authors also review Russian and foreign literature on this problem and their own data.